Humanizing Refugee Research in a Turbulent World - Bakewell, Oliver (Refuge)

(untitled) (Centre for Refugee Studies, York University, 2021)
This essay adopts a critical perspective of the idea of humanizing refugee research. It argues that much social scientific research is intrinsically dehumanizing, as it simplifies and reduces human experience to categories and models that are amenable to analysis. Attempts to humanize research may productively challenge and unsettle powerful and dominant hegemonic structures that frame policy and research on forced migration. However, it may replace them with new research frameworks, now imbued authority as representing more authentic or real-life experiences. Rather than claiming the moral high ground of humanizing research, the more limited, and perhaps more honest, ambition should be to recognize the inevitable dehumanization embedded in refugee research and seek to dehumanize differently.